1992
DOI: 10.1111/j.1365-3024.1992.tb00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Leishmania specific cell mediated and humoral immunity in asymptomatic dogs

Abstract: An ELISA and a lymphocyte proliferation assay were used for the detection of anti-Leishmania antibodies and parasite specific cellular immunity respectively in a preliminary study of canine leishmaniasis in Oporto, Portugal. A high rate of infection was found considering the comparatively small group sampled. Of 34 dogs examined two had anti-leishmanial antibodies but their lymphocytes did not proliferate in the presence of Leishmania infantum. Conversely two dogs demonstrated antigen specific lymphocyte proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1
5

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 15 publications
1
44
1
5
Order By: Relevance
“…Since our regions are endem ic, this percentage could b e caused by sev eral factors: initial stages, latent form s o f the diseases; or non specific cross reactions. The deve lopm ent o f cellular immunity in dogs may b e the origin o f latent form o f the disease as has b een des cribed by Cabral et al, 1992;Pinelli et al, 1994. The high proportion o f dogs with antibodies ≥ 100 that are asymptomatics may b e caused at an initial stage o f the disease (Abranches et al, 1991), but their epidem io logical im portance is greater because they are poten tially infectious for sand flies (Alvar et al, 1994).…”
Section: Discussionmentioning
confidence: 96%
“…Since our regions are endem ic, this percentage could b e caused by sev eral factors: initial stages, latent form s o f the diseases; or non specific cross reactions. The deve lopm ent o f cellular immunity in dogs may b e the origin o f latent form o f the disease as has b een des cribed by Cabral et al, 1992;Pinelli et al, 1994. The high proportion o f dogs with antibodies ≥ 100 that are asymptomatics may b e caused at an initial stage o f the disease (Abranches et al, 1991), but their epidem io logical im portance is greater because they are poten tially infectious for sand flies (Alvar et al, 1994).…”
Section: Discussionmentioning
confidence: 96%
“…Studies of naturally infected dogs also suggest that factors inherent to the host contribute to the variability in outcome of infection. 13,24,26,27 In fact, most infection protocols in vaccination or treatment studies appear to be designed to overcome the natural resistance of many dogs and produce full-blown disease in a short time span by delivering a massive dose of parasites by the unnatural route of IV injection. 6,[14][15][16][17] Previous studies showed that experimental IV infection was more likely to lead to overt disease than intradermal inoculation, which typically led to subclinical infection.…”
Section: Discussionmentioning
confidence: 99%
“…The studies reviewed here imply that dogs are readily infected with ACL, but compared with canine ZVL, 110,112,113,137,138,[141][142][143][167][168][169][170][171][172] little is known about the clinical, parasitologic, and immunologic course of canine ACL infections. Combined with xenodiagnosis studies, this information could identify correlates of infectiousness, enabling putative dog control programs to maximize their effectiveness by focusing on those dogs which are infectious.…”
Section: Can Dogs Be Incriminated As Reservoir Hosts Of Human Acl?mentioning
confidence: 99%
“…38,57,61,[68][69][70]72,73,76,77,80,81,82,84,85,89,90,92,[94][95][96][97][99][100][101]103, Due to their logistic convenience and relatively high sensitivity, serologic tests are the standard tools for identifying Leishmania-infected dogs (Table 2). However, difficulties associated with the interpretation of seroprevalence data are 1) serology is prone to nonspecific cross-reactions (false-positives), e.g., due to Trypanosoma cruzi infection; 136 2) there may be a delay between infection and seroconversion (i.e., a prepatent period); 110,112,113,[137][138][139] 3) a fraction of infected dogs may never seroconvert; 137,[140][141][142] and 4) seroconversion may not be permanent. 113,137,143 Therefore, sensitivity and/or specificity of serologic tests with respect to infection can vary considerably, and may underestimate prevalence and incidence of infection, and thus the scale of the control problem.…”
Section: Can Dogs Be Incriminated As Reservoir Hosts Of Human Acl?mentioning
confidence: 99%